ANALISIS PENAWARAN INDUSTRI MEBEL DI KOTA PEKANBARU - Hutagalung Raya Martini Tri; Harahap Azwar; Iyan Yani Rita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted in Pekanbaru City. Industry, trade, services, health services and other activities, where the cycle of world change recently changed a lot especially in the field of woods that very rapidly, so a good target for the sale of distribution of furniture and also the demand for products and other industrial services in Pekanbaru City. With the aim to know and analyze the influence of price, production cost, and profit on furniture offer. The total population in this study is 36 ukm. The sample used in this research is 36. Using the census method, where the whole population becomes the sample. And data processing using multiple linear regression method with SPSS program. Based on the results of the test if the data using multiple linear regression can be taken several conclusions, namely: Price has a positive and unsignificant influence on furniture supply. Production cost have a positive and significant effect on furniture offerings. Profit has a positive and significant effect on furniture offerings. And price, production cost, and profit have influence together to furniture offer in Pekanbaru City. Based on the analysis of factors affecting the supply of furniture, the effect of price, production cost, and profit can be given the following suggestions: a) The company needs to determine the pricing strategy, by stepping up and maintaining the quality and service for customer satisfaction. b) The Company may increase the amount of bid to raise profit by taking into account market conditions.Keywords: Price, Production Cost, Profit and Supply